EXPRESSIVE READING OF FAIRY TALES AS A MEANS OF DEVELOPING ORAL SPEECH IN PRIMARY SCHOOL STUDENTS (Web of Teachers: Inderscience Research, 2025)
In modern educational practice, the development of students’ oral speech and communicative competence is considered one of the key objectives of primary education. Fairy tales play a significant role in achieving this goal, as they contribute to vocabulary enrichment, emotional expression, and the formation of coherent speech. This article explores the pedagogical potential of expressive reading of fairy tales in developing oral speech among primary school students. The study analyzes effective teaching methods such as reading aloud, role-playing, retelling, and dramatization, and reveals their impact on students’ speech activity, confidence, and creative thinking. The findings indicate that systematic use of expressive reading techniques enhances students’ pronunciation, intonation, and overall communicative competence.